Clinical Outcomes of Corrective Fusion Surgery From the Thoracic Spine to the Pelvis for Adult Spinal Deformity at 1, 2, and 5 years Postoperatively. Issue 11 (1st June 2022) - Arima, Hideyuki; Hasegawa, Tomohiko; Yamato, Yu; Yoshida, Go; Banno, Tomohiro; Oe, Shin; Mihara, Yuki; Ide, Koichiro; Watanabe, Yuh; Nakai, Keiichi; Kurosu, Kenta; Matsuyama, Yukihiro
Abstract : We investigated patient-reported outcomes (PROs) at baseline and at 1, 2, and 5 years after corrective fusion surgery from the thoracic spine to the pelvis for adult spinal deformity. Two-year post-operative PROs were strongly correlated with 5-year post-operative PROs, indicating that 2-year PROs can predict longer-term outcomes. Abstract : Study Design: Retrospective cohort study. Objective: To investigate whether patient-reported outcomes (PROs) were consistent at 2 and 5 years after corrective fusion surgery from the thoracic spine to the pelvis in patients with adult spinal deformity (ASD) and to analyze whether revision surgery affected long-term outcomes. Summary of Background Data: PROs up to 2 years after corrective surgeries for ASD have been well-studied, but there are few reports of mid- to long-term results. Methods: We retrospectively analyzed patients with ASD who underwent corrective fusion surgery from the thoracic spine to the pelvis between 2010 and 2015. We investigated radiographic parameters and PROs (Scoliosis Research Society 22r [SRS-22r], Oswestry Disability Index [ODI]) preoperatively and at 1, 2, and 5 years postoperatively, and the correlations between PROs at these time points. We also compared changes in PROs at 5 years in patients who underwent revision surgery and those who did not. Results: A total of 131 patients who underwent corrective fusion surgery from the thoracic spine to the pelvis were analyzed. The PROs at 1 and 5 years after surgery showed significant correlations in all SRS-22r domains (function [ r  =  0.620], pain [ r  =  0.577], self-image [ r  =  0.563], mental health [ r  =  0.589], subtotal [ r  =  0.663], and ODI [ r  =  0.654]). The PROs at 2 and 5 years after surgery showed significantly strong correlations in all domains (function [ r   =  0.715], pain [ r   =  0.678], self-image [ r   =  0.653], mental health [ r  =  0.675], subtotal [ r  =  0.741], and ODI [ r  =  0.746]). There were no significant differences in the change in PROs at 5 years in any domain in patients who underwent revision surgery (all P   >  0.05). Conclusion: One-year postoperative PROs improved significantly. Two-year PROs correlated strongly with 5-year postoperative PROs, indicating that 2-year PROs can predict longer term outcomes. The need for revision surgery did not influence the mid- to long-term clinical outcomes of corrective fusion surgery for ASD. Level of Evidence: 3